Improving Teacher Competence Through Curriculum Alignment Training Programs and Competency Tests for Prospective Assessors PT. Daihatsu at Islamic’s VHS 1 Blitar - Thoifatu Sholihah; Yoto Yoto; Widiyanti Widiyanti (Didaktika: Jurnal Kependidikan, 2024)
A teacher is required to be able to develop competence and update the latest information technology. One form of technology update that can be done by teachers is participating in training programs.. This research uses a qualitative approach by carrying out the type of case study research. The results showed that training planning can be done in several stages. The first stage is the administrative and scheme preparation stage carried out by the committee together with representatives from PT Daihatsu East Java. The implementation of training begins with the socialization of the industrial curriculum, in this program teachers are introduced to industrial competencies which are used as material for curriculum alignment. The next training is the assessment of prospective competency test assessors. The process of becoming a competency test assessor involves several important stages. Prospective assessors must take part in training and examinations organized by PT Daihatsu in the Pintar Bersama Daihatsu (PBD) program. The final result of the assessment of prospective assessors is proven by an assessor certificate that can be used to guarantee the quality of student graduation when conducting competency tests at school.